Alterity in Autobiography: Charles Lamb’s "The Essays of Elia" - Çapkın, Nazım (English Studies at NBU, 2024)
This article scrutinizes the unorthodox turn in Charles Lamb’s autobiographical writing through the figure of Elia with its potential to test the limits of alterity and one’s representation of oneself while challenging at the same time the immunity of self as the origin of knowledge and truth. In so doing, this study also maintains that Elia as the autonomous entity calls into question the authority of the writer as well as any claim on teleology and coherence in the act of writing one’s own life specifically. To this end, explication of some of the key passages in the essays is informed by Jacques Derrida’s theoretical stance towards autobiography in his seminal work The Ear of the Other. In this vein, the article suggests that Elia’s individuality and self-consciousness in the essays manifest in unorthodox ways the simultaneous interpretative potential of the figure as the reader of Lamb’s life in making.